Risk factors for osteoradionecrosis of the jaw in patients with oral or oropharyngeal cancer: Verification of the effect of tooth extraction before radiotherapy using propensity score matching analysis - Yuka Kojima; Mitsunobu Otsuru; Takumi Hasegawa; Nobuhiro Ueda; Tadaaki Kirita; Shin-ichi Yamada; Hiroshi Kurita; Yasuyuki Shibuya; Madoka Funahara; Masahiro Umeda (Elsevier, 2022)
Background/purpose: Osteoradionecrosis of the jaw (ORN) often occurs in patients with head and neck cancer undergoing radiotherapy (RT). It has been recommended to extract the tooth before RT that may become source of infection, but in recent years, some investigators have reported that tooth extraction before RT increase the risk of developing ORN and therefore should be avoided. The purpose of the study is to evaluate the risk factors for ORN including tooth extraction before RT. Materials and methods: This was a retrospective study of 366 patients with oral or oropharyngeal cancer who underwent RT of 50 Gy or more at six university hospitals, with follow-up of at least six months post-RT. The relationship between each factor and ORN incidence was analyzed using the Cox proportional hazard model. Results: Periapical lesions, more than 50% loss of alveolar bone, and tooth extraction after RT significantly correlated with ORN. Intensity-modulated RT showed a lower incidence than three-dimensional conformal RT, although not statistically different. Tooth extraction before RT significantly reduced ORN incidence, after adjusting the background factors using propensity score matching. Conclusion: In patients with oral or oropharyngeal cancer who underwent RT, periapical lesions, more than 50% loss of alveolar bone, and tooth extraction after RT significantly increased the risk for ORN. Infected tooth extraction before RT significantly reduced the risk.